2022
DOI: 10.1021/acsapm.2c01172
|View full text |Cite
|
Sign up to set email alerts
|

Remarkably Enhanced Energy Storage Performances in Well-Designed Core–Shell Ag@TiO2–Poly(vinylidene fluoride) Nanocomposites

Abstract: Designing and regulating the microstructure of core−shell fillers are effective ways to fabricate polymer-based nanocomposites with excellent energy storage performances. Along this line, the unique structure combination of 0D metallic Ag nanoparticles (NPs) and 1D bark-like TiO 2 nanowires (NWs) were successfully prepared. Through regulating the volume fraction of Ag NPs (x vol %) in the Ag@TiO 2 NWs, the polarization and breakdown strength of Ag@TiO 2 /PVDF nanocomposites have been optimized, which is eviden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…The M′′ spectra of the PMMA and Mg 0.5 Ni 0.5 Fe 2 O 4 /PMMA nanocomposite films showed distinct relaxation peaks within the frequency range of 100 Hz to 1 kHz [60][61][62]. These peaks can be attributed to the β-relaxation process, namely the rotation of the ester side groups (-COOCH 3 ) in the repeat units of the PMMA chain, as explained in tan (δ) spectra [51][52][53]. The M′′ relaxation peaks have shifted somewhat towards higher frequencies, as relaxation peaks in tan (δ) except in 4 wt% Mg 0.5 Ni 0.5 Fe 2 O 4 /PMMA sample shows the reverse behavior, which is a common characteristic observed in the dielectric and modulus loss functions of several PNC materials [62][63][64][65][66].…”
Section: Dielectric Propertiesmentioning
confidence: 83%
See 1 more Smart Citation
“…The M′′ spectra of the PMMA and Mg 0.5 Ni 0.5 Fe 2 O 4 /PMMA nanocomposite films showed distinct relaxation peaks within the frequency range of 100 Hz to 1 kHz [60][61][62]. These peaks can be attributed to the β-relaxation process, namely the rotation of the ester side groups (-COOCH 3 ) in the repeat units of the PMMA chain, as explained in tan (δ) spectra [51][52][53]. The M′′ relaxation peaks have shifted somewhat towards higher frequencies, as relaxation peaks in tan (δ) except in 4 wt% Mg 0.5 Ni 0.5 Fe 2 O 4 /PMMA sample shows the reverse behavior, which is a common characteristic observed in the dielectric and modulus loss functions of several PNC materials [62][63][64][65][66].…”
Section: Dielectric Propertiesmentioning
confidence: 83%
“…The MWS polarization arises from the interfaces between the insulator and conductor. The increase in the dielectric constant can be explained by analyzing the formation of mini-capacitor networks in the Mg 0.5 Ni 0.5 Fe 2 O 4 /PMMA nanocomposite films as the Mg 0.5 Ni 0.5 Fe 2 O 4 nanoparticle concentration gradually increases compared to pure PMMA [51,52].…”
Section: Dielectric Propertiesmentioning
confidence: 99%
“…For example, Wang et al compared the dielectric properties of polymer composites containing 0D Al 2 O 3 nanoparticles and 1D nanowires and found that 1D nanowires can increase the potential shift while maintaining a high breakdown electric field at a much lower concentration . As a result, 1D NaNbO 3 nanowires/polymer composites are very promising candidates to achieve great dielectric properties while maintaining the flexibility of materials at a smaller filler content. …”
Section: Introductionmentioning
confidence: 99%
“…Ceramic materials have higher dielectric constants but tend to have lower breakdown strengths, complementing the electrical properties of polymer materials [ 35 ]. To improve the electrical properties of polymers, ceramic materials with high dielectric constants are added to polymer matrices to form ceramic/polymer composites [ 36 , 37 , 38 , 39 , 40 , 41 , 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…The main means of improving the dielectric and energy storage properties of polymers are multilayered, but the preparation process is complex and not suitable for commercialization. Single-layer films doped with conductive substances, such as metal ions and carbon nanotubes [ 49 , 50 ], have been studied for insulating materials such as doped ceramics [ 36 , 37 , 38 , 39 , 40 , 41 , 42 ], but there is less literature on semiconductor high-entropy materials as a filler phase with which to modify PVDF-based semicrystalline polymers. Some literature has shown that spinel ferrite can improve dielectric and breakdown properties [ 51 , 52 ].…”
Section: Introductionmentioning
confidence: 99%